Decisional Regret in Women Receiving High-Risk Results From Non-Invasive Prenatal Genetic Screening [24B]. (May 2017) - Allyse, Megan
Abstract : INTRODUCTION: Non-invasive prenatal testing (NIPT) panels have expanded rapidly from limited aneuploidy screening for trisomy 21 to expanded screening for aneuploidies and abnormalities, including sex chromosome aneuploidies and, recently, microdeletions. This study sought to understand the experiences of women receiving NIPT results and the effect of high-risk, false, or inconclusive results on maternal anxiety and pursuit of additional testing. METHODS: 40 semi-structured telephone interviews were conducted with women who were currently or had recently been pregnant and received high risk (n=15), false positive/negative (n=19), or inconclusive (n=5) results from NIPT. RESULTS: Many women felt deceived by the advertised "99% accuracy" statistic of NIPT and asserted that much of their post-test anxiety could have been prevented by improved pre-test counseling. Several women felt pressured by providers to terminate, and most felt pressured to pursue invasive diagnostic testing. False results from NIPT had significant lasting effects the remainder of their pregnancies, their willingness to have more children, and their openness to doing NIPT again. Most women would not do NIPT in future pregnancies or would only do it if the panel was smaller. CONCLUSION: Findings suggest significant concerns about how clinical practices are integrating NIPT. Study participants indicate problems with the dialogue when NIPT is offered, the return of results, and the positive predictive value of expanded screenings. Given the confusion about NIPT accuracy, the prevalence of follow-up invasive tests, and the large number of women who regret doing NIPT, NIPT offering and the delivery of results need to be carefully approached.